Caracterização da deposição balística bidispersa em 2 e 3 dimensões - Silveira, Flávio Alexandre da (2014)
We analyze the bi-disperse ballistic deposition model (DBB), in which deposition of two diferent sizes of particles, accounting for a random and a correlated component, compete. The aggregation of particles of the latter type (bigger grains) causes latteral growth, which tipically characterizes Kardar-Parisi-Zhang (KPZ) growth, while particles of the first type aggregate following the rules of random deposition (DA). We argue that DBB exhibits the same scaling behaviour as other competitive growth models involving DA and some other correlated component. In two and three dimensions, we study the relationship between the parameter F, related to the proportion between the two types of grain, the crossover time from random to correlated growth (applying scaling arguments to the coeficients of surface width, in diferent growth regimes, as in a previous work), and the coeficients of the stochastic equation of motion. The conclusions are supported by results of numerical simulations in d = 1 + 1 and d = 2 + 1 dimensions. The steady-state roughness distributions have proved to be very useful in the discussion of the universality class of these deposition models. We also studied the geometric properties of the exposed surface and the percolation transition of the porous deposits. We observe that the porous media percolate even for very small cocentrations of the bigger grains, in contrast to related growth models of porous deposits.